Seroprevalence of brucellosis in different animal species of Kailali district, Nepal - Pandeya, YR; Joshi, DD; Dhakal, S; Ghimire, L; Mahato, BR; Chaulagain, S; Satyal, RC; Sah, SK (International Journal of Infection and Microbiology, 2013)
Introduction: Brucellosis is a contagious disease of livestock with significant economic impact. It is also a zoonotic disease, highly infectious for humans causing a disease called undulant fever or Malta fever. This study was carried out to determine the sero-status of Brucella spp. infection in cattle (cows), buffalo and goat in Kailali district of Far Western Region of Nepal. Materials and Methods: This cross-sectional study was conducted in Kailali district of Nepal during a period from September, 2012 to January, 2013. A total of 233 animal blood samples (50 Cattle, 67 Buffalo and 116 Goat) were collected and tested for Brucella antibody by plate agglutination test (PAT). Results: The seroprevalence of Brucellosis was 12% (28/233). Thirty two percentage (16/50) of cattle, 13.4% (9/67) of buffaloes, and 2.6% (3/113) goats were sero positive (p<0.05). Seroprevalence was higher in females (14.6% vs. 10.6%) (P>0.05) and was higher in younger cattles and older buffalo and goats (p>0.05). Conclusions: This study showed that brucellosis exists as a potential threat in animals of Kailali district. This could be a potential source of infection to humans. Considering the high economic losses it can impart on livestock sector and the possible human health abnormalities, timely facilitation of awareness generation program and adoption of proper prevention and control strategies are recommended. DOI: http://doi.dx.org/10.3126/ijim.v2i1.8005 Int J Infect Microbiol 2013;2(1):22-25